The Development of Technical Treatments for Flashback in Cinematographic Mediator - Ahmed, Maha Faisal; Mohammed, Mohammed Sameer (Al-Adab Journal, 2020)
The development cannot abandon technical-artistic creativity, and each art has its own language and its working tools by which the artist can communicate his ideas, so he can be creative in forming and formulating them within artistic treatments that contribute to enriching the visual image and the subject expressed, and it is from this idea that the research sheds light on the development Technical treatments for scenes of flashback in the cinematographic environment, which enter among the various technical treatments employed by the director, and contribute to creating appropriate and expressive influences and inspirations within the course of the flashback scene to include time indications related to the structure of time in the cinematographic work, and after the digital world entering the film and television milieu, this milieu have benefited from employing new techniques to scenes associated with flashback goals, which contributed to the diversification process at work and address various technical treatments on the level of form in the presentation of the flashback scene.